Estudio de patrones de comportamiento y actividad del jaguar negro (panthera onca) en el zoológico de Santacruz - Tequendama – Cundinamarca (2022)
The black jaguar (Panthera onca) is the largest cat in the American continent. (Seymour, 1989). It lives mainly in the jungles (Herrera et al. 2018), areas of water, forests along to the river (Garcia, 2006) or mangroves (Herrera et al, 2018). They can be found mainly in South American countries. They are carnivorous animals (Swank & Teer 1989), solitary (Seymour, 1989) and generally nocturnal (Oliveira, 1994). In the case of animals in captivity, they usually present stereotypes due to stress, frustration and lack of stimulation (Manson, 1991), since they do not can perform their natural behavior (Mendoza, 2003; Deem and Karesh, 2005; Tempesta et al. al., 2005). These stereotypes can be diminished with environmental enrichment, which can to be; social, cognitive, structural, sensory and nutritional. The ethogram allows us to see and demonstrate alterations in what should be their normal behavior and measure the variables that are seen confronted by the animal and its keepers (Manteca and Salas, 2015)